MO498INSIDE CKD: MODELLING THE CLINICAL AND ECONOMIC IMPACTS OF TARGETED URINARY ALBUMIN-TO-CREATININE RATIO SCREENING IN EUROPEAN COUNTRIES. (29th May 2021) - Garcia Sanchez, Juan Jose; Abdul Sultan, Alyshah; Ärnlöv, Johan; Cabrera, Claudia; Card-Gowers, Joshua; De Nicola, Luca; Halimi, Jean-Michel; Mennini, Francesco Saverio; Navarro-González, Juan F; Nolan, Stephen; Power, Albert John; Retat, Lise; et al.
Abstract: Background and Aims: With an estimated global prevalence of 10% or more, chronic kidney disease (CKD) and its associated complications constitute a major challenge for healthcare systems worldwide, which is worsened by the burden of undiagnosed CKD. Early diagnosis of CKD followed by guideline-recommended interventions can improve patient outcomes, particularly by delaying or preventing progression to kidney failure. This may result in a reduction in the costs associated with managing CKD. Elevated albuminuria is a strong predictor of risk of complications and death in patients with CKD, and measurement of urinary albumin-to-creatinine ratio (UACR) is an important diagnostic and prognostic tool. However, adherence to screening recommendations is suboptimal in routine care. Inside CKD aims to model the global clinical and economic burden of CKD using country-specific, patient-level microsimulation models. We used the Inside CKD microsimulation to model the potential clinical and economic impacts of routine UACR measurement with appropriate intervention in primary care settings in UK patients aged 45 years and over. This analysis is being expanded to further European countries. Method: We used the Inside CKD microsimulation to model the clinical and economic impacts of measuring UACR with subsequent appropriate intervention during routine primary care visits in all individuals aged 45 years and over, versus current practice (i.e. screening in patients with diabetes, hypertension or cardiovascular disease). The model covers the period 2020–2025. First, a virtual population representing the general population of the UK was constructed using data from the 2016 Health Survey for England, covering demographics, prevalence of CKD and comorbidities (type 2 diabetes, uncontrolled hypertension and heart failure) and incidence of complications (heart failure, myocardial infarction, stroke and acute kidney injury). The model also included parameters relating to the direct and indirect costs associated with CKD (e.g. cost of renal replacement therapy), the proportion of patients who visit a primary care physician at least once a year, the proportion of patients who agree to UACR measurements, and the diagnostic sensitivity and specificity of UACR measurements. Results: Preliminary results from the UK show that over the 2020–2025 period, routinely measuring UACR in all patients aged 45 years and over during primary care visits could prevent progression to CKD stages 3b–5 in approximately 327 000 patients, compared with current clinical practice, with a linear increase in the cumulative number of prevented cases over the 5 years (Figure ). Associated savings in costs related to the management of CKD and its complications are projected to be approximately £300M in 2025, corresponding to a 1.9% reduction from current clinical practice. Conclusion: Preliminary results from this Inside CKD microsimulation model show that implementation of routine measurement of UACR in primary care settings in the UK could prevent a substantial number of patients progressing to CKD stages 3b–5 and has the potential to reduce the associated healthcare-related costs considerably. This analysis is being extended to other European countries.